خصائص وأنواع الدليل الإلكتروني في الكويت ودول المقارنة - الدويش، بندر عقاب جفين كميخ حطاب (جامعة القاهرة - كلية الحقوق - فرع الخرطوم, 2023)
أن تسارع إيقاع التقدم التكنولوجي والتقني الهائل، وظهور الفضاء الإلكتروني ووسائل الاتصالات الحديثة كالفاكس والإنترنيت وسائر صور الاتصال الإلكتروني عبر الأقمار الصناعية كانوا وسيلة استغلها مرتكبو الجرائم الإلكترونية، في تنفيذ جرائمهم التي لم تعد تقتصر على إقليم دولة واحدة، بل تجاوزت حدود الدول، وهي جرائم مبتكرة ومستحدثة تمثل ضربا من ضروب الذكاء الإجرامي، استعصى إدراجها ضمن الأوصاف الجنائية التقليدية في القوانين الجنائية الوطنية والأجنبية. ومن حيث ما يرتبط بهشاشة نظام الملاحقة الإجرائية التي تبدو قاصرة على استيعاب هذه الظاهرة الإجرامية الجديدة، سواء على صعيد الملاحقة الجنائية في إطار القوانين الوطنية أم على صعيد الملاحقة الجنائية الدولية، مما أوجب تطوير البنية التشريعية الجنائية الوطنية بذكاء تشريعي مماثل تعكس فيه الدقة الواجبة على المستوى القانوني وسائر جوانب وأبعاد تلك التقنيات الجديدة، بما يضمن في الأحوال كافة احترام مبدأ شرعية الجرائم والعقوبات من ناحية، ومبدأ الشرعية الإجرائية من ناحية أخرى، وتتكامل فيه في الدور والهدف مع المعاهدات الدولية. ويعد الإثبات الجنائي بالأدلة الرقمية من أبرز تطورات العصر الحديث، والتي جاءت لتلائم الثورة العلمية والتكنولوجية والتقنية في عصرنا الحالي، والتي تطور معها الفكر الإجرامي الذي صاحب ظهور ما يعرف بالجريمة الإلكترونية ألقى على عاتق القائمين على مكافحة الجريمة في الدولة عبئا شديدا ومهاما جسيمة تفوق القدرات المتاحة لهم وفق أسس وقواعد وإجراءات البحث الجنائي والإثبات الجنائي التقليدي، نظرا لعدم كفاية وعدم ملائمة هذه النظم التقليدية في إثبات تلك الجرائم سواء من الناحيتين القانونية أو التقنية، الشيء الذي ألزم على المشرع أن يتدخل بقوانين تتناسب مع مثل هذه الجرائم. فكانت هذه التطورات التي عرفتها المعلوميات كفيلة لتجعل الإثبات الجنائي يتأثر من جراء الجرائم التي أفرزتها هذه الثورة المعلوماتية، الأمر الذي جعل من طبيعة الإثبات بالوسائل التقليدية أمر متجاوز. ولعل هذه الطبيعة غير المرئية للأدلة المتحصلة من الوسائل الإلكترونية تلقى بظلالها على الجهات التي تتعامل مع الجرائم التي تقع بالوسائل الإلكترونية حيث تصعب قدرتهم على فحص واختبار البيانات محل الاشتباه خاصة في حالات التلاعب في برامج الحاسوب، ومن ثم فقد يستحيل عليهم الوصول إلى الجناة. فمن المعلوم أن جهات التحري والتحقيق اعتادت على الاعتماد في جمع الدليل على الوسائل التقليدية للإثبات الجنائي التي تعتمد على الإثبات المادي للجريمة ولكن في محيط الإلكترونيات فالأمر مختلف، فالمتحري أو المحقق لا يستطيع أي منهما تطبيق إجراءات الإثبات التقليدية على المعلومات المعنوية. The tremendous technological and technical development, cyberspace science and modern means of communication using satellites and electronic transmitters, in carrying out its crimes, which are commercial projects, are considered commercial projects, one country, crimes that have exceeded, and they are commercial and innovative projects that represent a kind of criminal intelligence, use it within the traditional descriptions in national and foreign laws. And in terms of what is related to the fragility of the procedural prosecution system, which seems limited to absorbing this new criminal phenomenon, whether at the level of criminal prosecution within the framework of national laws or at the level of international criminal prosecution, which necessitated the development of the national criminal legislative structure with similar legislative intelligence that reflects the due accuracy at the level In all cases, the principle of legality of crimes and penalties on the one hand, and the principle of procedural legality on the other hand, is respected in all cases, and is complementary in role and purpose with international treaties. Criminal evidence with digital evidence is one of the most prominent developments of the modern era, which came to suit the scientific, technological and technical revolution of our time, and with which the criminal thought that accompanied the emergence of what is known as cybercrime has developed, has placed a heavy burden on those in charge of combating crime in the country. Heavy tasks that exceed the capabilities available to them according to the foundations, rules and procedures of criminal investigation and traditional criminal evidence, due to the inadequacy and inadequacy of these traditional systems in proving these crimes, whether from a legal or technical point of view, which obligated the legislator to intervene with laws commensurate with such crimes. These developments in informatics were sufficient to make criminal evidence affected by the crimes produced by this information revolution, which made the nature of proof by traditional means transcendental. Perhaps this invisible nature of the evidence obtained from electronic means casts a shadow on the parties that deal with crimes that occur by electronic means, as it is difficult for them to be able to examine and test the suspected data, especially in cases of tampering with computer programs, and therefore it may be impossible for them to reach the perpetrators. It is well known that investigation and investigation authorities used to rely on traditional means of criminal proof that rely on physical evidence of the crime, but in the vicinity of electronics, the matter is different. Neither of them can apply traditional evidentiary procedures to intangible information.
Keywords: الجرائم الإلكترونية -- الأدلة الرقمية -- الإثبات الجنائي -- القانون الكويتي